The Role of Soft Law in Functioning of Supranational Competition Networks (Contemporary Central & East European Law, 2020)
The article discusses the issue of soft law and its role in the functioning of supranational competition networks. It draws from the assumption that international cooperation is crucial for competition authorities around the world and that the most efficient and comprehensive form of such cooperation takes the form of supranational competition networks. For networks, establishing common standards in the form of soft law is essential for development of the network and the deepening of cooperation between network members. The article concludes that supranational soft law has its eminent advantages like informality, flexibility, and accessibility which allow it easily to respond to the changing needs of authorities and stakeholders, and to adapt to evolution of the economic and regulatory environment. However, the problems of legitimacy and transparency in the process of establishing soft law rules are yet to be resolved.